2022
DOI: 10.1108/ijopm-02-2022-0100
|View full text |Cite
|
Sign up to set email alerts
|

The impact of servitization on trade credit in manufacturing firms: a signaling theory perspective

Abstract: PurposeThe aim of this study is to empirically test the link between servitization and trade credit in manufacturing firms as well as the boundary conditions of this link.Design/methodology/approachUsing a unique dataset of 4,974 observations covering 838 manufacturing firms publicly listed in the United States during 1990–2020, this study examines the impact of servitization on trade credit and the moderating impacts of financial slack and service relatedness based on fixed-effect regression models.FindingsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…, 2022), whereas breadth of servitization is considered as the innovation of service types and models (Benedettini et al. , 2017; Wang et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022), whereas breadth of servitization is considered as the innovation of service types and models (Benedettini et al. , 2017; Wang et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…degree and breadth). Degree of servitization refers to the improvement of service quality and customer satisfaction (Guedes et al, 2022;Zhang et al, 2022), whereas breadth of servitization is considered as the innovation of service types and models (Benedettini et al, 2017;Wang et al, 2023). Specifically, we summarize the mixed findings reported in previous studies on the relationship between servitization and firm performance through the literature review, and point out that both degree and breadth of servitization can improve firm performance through the hypothesis development and the empirical tests.…”
Section: Theoretical Contributionsmentioning
confidence: 95%
“…This study enriches the content of signals in predicting SCFP. Extant studies employing signaling theory have tested some capability signals, such as network capability and servitization capability (Song et al ., 2020; Wang et al ., 2023). This study empirically examines how innovation capabilities help SMEs to be better and more easily identified by FSPs (Song et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In reality, FSPs can be financial institutions or supply chain focus enterprises; they are not limited to a specific type of entity (Song et al ., 2018). Existing literature has mainly focused on the operation mode (Wang et al ., 2023; Lu et al ., 2022b; Yan and Sun, 2015), risk management and control (Xu et al ., 2018), information technology application (Lu et al ., 2020; Song et al ., 2021), network structure (Jhang et al ., 2021; Steven et al ., 2019), innovation capabilities (Lu et al ., 2020; Fabbri and Klapper, 2016; Qiao and Zhao, 2023), supply chain collaboration (Pfohl and Gomm, 2009), the overall operation efficiency of the supply chain (Filbeck et al ., 2016) and other aspects of supply chain finance (Beka Be Nguema et al. , 2021b; Elliot et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Song et al (2020) suggested that firms can obtain more financing support through signals reflecting their operational capabilities and network embeddedness. Wang et al (2023a) considered the firm's servitization conveying two conflicting messages to suppliers in the context of trade credit: stronger buyer-supplier relationships and higher operational risks. While shedding light on the function of signals for a singular receiver, these empirical studies have yet to fully capture the multifaceted role of the same signal (i.e.…”
Section: Signaling Theorymentioning
confidence: 99%